Morphometric of Mole Crabs (Anomura: Hippidae) from Ambon Island, Indonesia - Hasan Tuaputty; Fredy Leiwakabessy; Alwi Smith; Eifan Boyke Pattiasina; Muhammad Tarmizi Kubangun (BIOPENDIX, 2026)
In Maluku, mole crabs are only used as food ingredients by a small number of coastal communities. In Seilale Village, Nusaniwe District, Ambon Island, mole crabs (called "hotong") are processed by grilling or burning using skewers or thin wood, stirfried with kang vegetables, or fried. The regressions used are from the species of Hippa ovalis, H. marmorata and H. celaeno. This research was conducted in the waters of Rumahkay, Haria, and Amahusu Villages Morphometry results and growth analysis with allometry also showed a linear relationship on the growth of each species. Relevant results from the study showed a significant nutrient content in mole crab Hippa genus. Mole crabs Hippa genus which has abundant unsaturated fatty acid makes mole crabs have become an alternative that has a potentially high economic value, an alternative source of nutrition from fish, and an alternative source for income to the local community specifically in coastal sandy beach areas in general